2018
DOI: 10.1172/jci.insight.99062
|View full text |Cite
|
Sign up to set email alerts
|

Aquaporin-1 regulates platelet procoagulant membrane dynamics and in vivo thrombosis

Abstract: In response to collagen stimulation, platelets use a coordinated system of fluid entry to undergo membrane ballooning, procoagulant spreading, and microvesiculation. We hypothesized that water entry was mediated by the water channel aquaporin-1 (AQP1) and aimed to determine its role in the platelet procoagulant response and thrombosis. We established that human and mouse platelets express AQP1 and localize to internal tubular membrane structures. However, deletion of AQP1 had minimal effects on collagen-induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(58 citation statements)
references
References 60 publications
2
53
3
Order By: Relevance
“…Our results are consistent with the previous report showing that platelets from children with a mutation of AQP7 have impaired ATP secretion from dense granules (Goubau et al, 2013). In the very recently published paper, Agbani et al demonstrated that platelets from AQP1 knockout mice have only slightly impaired secretion from the dense granules (Agbani et al, 2018). This was interpreted to mean that AQP1 is not directly involved in the platelet secretory response.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our results are consistent with the previous report showing that platelets from children with a mutation of AQP7 have impaired ATP secretion from dense granules (Goubau et al, 2013). In the very recently published paper, Agbani et al demonstrated that platelets from AQP1 knockout mice have only slightly impaired secretion from the dense granules (Agbani et al, 2018). This was interpreted to mean that AQP1 is not directly involved in the platelet secretory response.…”
Section: Discussionsupporting
confidence: 93%
“…The results presented here suggest that besides recently discovered AQP1 (Agbani et al, 2018) and AQP7 (Goubau et al, 2013), human platelets are likely to possess ten additional subtypes of AQP family members belonging to the subfamilies of classical aquaporins (AQPs 0-2 and AQPs 4-6), aquaglyceroporins (AQP3, AQP7, AQP9 and AQP10) and superaquaporins (AQP11 and 12) (Fig. 1A).…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Intriguingly, treatment of platelets with Au(III) did not affect the generation of a calcium signal in thrombin-or collagen-activated platelets notably (Figure 11), a well-accepted prerequisite for the development of platelet procoagulant response (Varga-Szabo et al, 2009;Obydennyy et al, 2016). Our observation is contrary to those obtained by Agbani et al (2018), where authors observed diminished calcium signal in platelets from AQP1-null mice adhered to collagen. Possible explanation To investigate effect of HAuCl 4 on platelet ballooning, platelets (in whole blood) preincubated without (−Au) or with (+Au) HAuCl 4 (100 μM) were allowed to adhere to a collagen-coated surface under shear rate of 1,000 s −1 , followed by 4 min staining with Alexa Fluor 647-ANX V (1:200).…”
Section: Engagement Of Aqps In Platelet Procoagulant Responsecontrasting
confidence: 97%
“…Alternatively, mitochondrial depolarization (70), scramblase activity (146,147), or water entry into platelets (33,148) are potential targets to inhibit formation of the thrombin-generating subpopulation of platelets while still allowing platelet aggregation to occur. It may be that inhibition of procoagulant platelet formation could be an alternative approach to reduce thrombosis without impairing hemostasis.…”
Section: Conclusion: Potential Of Procoagulant Phosphatidylserine-expmentioning
confidence: 99%